Evaluation of the Organic Acids Ability for Extraction of Anthocyanins and Phenolic Compounds from Different Sources and Their Degradation Kinetics During Cold Storage - Hosseini Sepideh; Gharachorloo Maryam; Ghiassi-Tarzi Babak; Ghavami Mehrdad (Polish Journal of Food and Nutrition Sciences)
The study of anthocyanin and phenolic acids has always received much attention due to their extensive range of colors and potential beneficial health effects. In this study extraction of anthocyanins from barberry, eggplant peel and red cabbage was investigated by using different organic solvents. Soluble solid content, antioxidant capacity, total monomeric anthocyanins and total phenolic content were determined and then degradation kinetics of anthocyanin in different solution during freezing process was assayed. In order to examine the effect of different acids on the degree of extraction of anthocyanin and total phenol, varied concentration of hydrochloric, citric and acetic acids were dissolved in a mixture of water and ethanol to prepare acidified aqueous solution. Results indicated that citric acid solution is one of the best solvents for phenolic and anthocyanin extraction which showed the best scavenging activity of DPPH radical. Results from degradation kinetics of total monomeric anthocyanins revealed that stability of anthocyanins in the solution depended on temperature and other ingredients which are present in the medium. Moreover, the present data confirmed that barberry and red cabbage acidified extracts could be one of the more stable natural food colorants based on anthocyanins.